Built Heritage Meets Inclusive Design: Identifying Challenges And Strategies Through A Multiple Case Study Enquiry - Van de Bemdt, Lene; Heylighen, Ann; Eisazadeh, Negin (Protection of Cultural Heritage, 2024)
Inclusive design aims to accommodate as many people as possible by considering the diversity of human abilities and conditions during design. This raises challenges in relation to built heritage: proposals to make a building more inclusive may encounter objections from conservation authorities. Our research aims to (1) explore these tensions between the conservation of built heritage and the ambition to make the built environment more inclusive and (2) identify strategies that allow addressing them. Based on existing research, we first examined how the domains of inclusive design and built heritage conservation are related, where they conflict and strengthen each other, as well as how researchers with different backgrounds suggest to address them. Second, we studied six building projects where built heritage and inclusive design meet, all located in Flanders. Due to the coronavirus pandemic, we relied mainly on desk research. We identified challenges, tensions and issues that came forward in the development of these projects as well as strategies adopted to address them. Two case studies illustrate how built heritage can be an asset to provide high-quality care. The four remaining cases illustrate how KU Leuven university deals with the challenge of rendering its rich historic building patrimony more inclusive. Confronting the six cases makes clear that built heritage can be made more inclusive, and might even contribute to inclusive design, and that this involves a time consuming process with transdisciplinary input.